2022
DOI: 10.1002/cam4.5043
|View full text |Cite
|
Sign up to set email alerts
|

Major depression disorder may causally associate with the increased breast cancer risk: Evidence from two‐sample mendelian randomization analyses

Abstract: Introduction Major depression disorder (MDD) has been associated with increased breast cancer risk in epidemiological studies; however, it is still unknown whether this association is causal or not. The aim of this study is to determine the causal relationship between MDD and breast cancer risk. Methods Two‐sample Mendelian randomization (MR) analyses with 92 single‐nucleotide polymorphisms (SNPs) significantly associated with MDD as instrumental variables (IVs) were performed. Effects of these SNPs on breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 62 publications
1
11
1
Order By: Relevance
“…Depressive and anxiety disorders may share genetic diathesis [ 34 ]. A common genetic background has also been demonstrated between depression and some types of cancer [ 35 , 36 ]. A possible mediator of this common genetic background could be underlying personality traits (such as neuroticism and extraversion) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Depressive and anxiety disorders may share genetic diathesis [ 34 ]. A common genetic background has also been demonstrated between depression and some types of cancer [ 35 , 36 ]. A possible mediator of this common genetic background could be underlying personality traits (such as neuroticism and extraversion) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to previous researches, MR analyses may result in false positives if genetic correlations occur among exposures (35,36). Consequently, two methods, multivariable IVW and multivariable MR-Egger, were employed to carry out multivariable MR analyses on 1 https://gwas.mrcieu.ac.uk/ major depressive disorder and schizophrenia.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Among the potential elements that may additionally influence risks of breast diseases, mental factors are receiving growing attention (3). Previous researches have linked some mental ailments to an multiplied hazard of breast cancer (4,5). Several observational studies confirmed that major depressive disorder would possibly increase the incidence of breast cancer (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental disorders constitute a major contributor to disease and economic burden globally, with depressive disorders accounting for the largest proportion of disability-adjusted life-years from mental disorders in 2019. 1 As a long-term psychological condition, a growing body of studies has demonstrated that depressive symptoms are associated with the risk of various physical conditions, such as diabetes, 2 dementia, 3 cancer 4 and cardiovascular disease (CVD), 5 as well as mortality. 6 For instance, a pooled analysis of 563 255 participants found that baseline depressive symptoms, as measured by the Center for Epidemiological Studies-Depression Scale or the Patient Health Questionnaire-2 (PHQ-2), were associated with a higher risk of CVD incidence.…”
Section: Introductionmentioning
confidence: 99%